ONLINE LEARNING IN HIGHER INSTITUTIONS: EXPLORING CHALLENGES ON STUDENTS’ ENGAGEMENT - Aini Sofia Binti Jasmi; Siti Nurbalqis Binti Mohd Samsudin; Nur Ayza Farhana Binti Abas; Nur Zuhairah Binti Zamzuri; Munirah Binti Mohd Jidi; Nurul Izzah Binti Borhan (International Journal of Accounting, Finance and Business, 2022)
Over the past few years, a new pandemic has just spread to the point that it couldkill people suddenly. This outbreak is known as Coronavirus (COVID-19) and now it isbecoming endemic to most parts of the world. Many daily activities have been limited in orderto maintain the social distance that could spread the virus, including implementing theMovement Constraint Order (MCO). Eventually, we need to adapt to this situation and changeour ways of living our lives. One of them is the learning method and learning medium that needsto be transitioned from regular face to face learning to online learning. Learning at the highschool and university level, which is normally done physically, has transitioned to onlinelearning and this situation has put the educational system under change, forcing educators andlearners to adopt the online teaching methods. This paper aims at reviewing the literature onchallenges of online learning. Among problems or challenges faced by the students aredifficulties at communicating, stress in having online classes due to lack of resources andtechnology and few more. The review will give a holistic understanding of the online learningchallenges for future researchers and aid to identify the research gap.